1997
DOI: 10.1016/s0925-4439(97)00020-3
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito midgut glycoproteins and recognition sites for malaria parasites

Abstract: Midgut glycoproteins of the malaria vector Anopheles tessellatus were partially characterised by gel electrophoresis and lectin binding. Specific binding to wheat germ agglutinin (WGA) and Concanavalin A (Con A) indicated the presence of N-linked core oligosaccharides in many proteins. Rabbit antibodies were produced against wheat germ agglutinin binding proteins (WGABP). These antibodies also recognised distinct proteins in the peritrophic membrane which is secreted into the midgut to enclose a bloodmeal. Rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Because these were not observed, it is difficult to directly associate the CS protein phenotypes with the resistance process. Other possible unidentified molecular differences in early sporogonic stages of the parasite phenotypes may exist that, in interaction with each mosquito species' midgut structure 27 and physiology, [28][29][30] could determine mosquito species-specific parasite infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Because these were not observed, it is difficult to directly associate the CS protein phenotypes with the resistance process. Other possible unidentified molecular differences in early sporogonic stages of the parasite phenotypes may exist that, in interaction with each mosquito species' midgut structure 27 and physiology, [28][29][30] could determine mosquito species-specific parasite infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that the carbohydrate on the mosquito microvillar surface might serve as a receptor for the initial association between the malaria parasites and the gut epithelial cells. Ramasamy et al (13,14) found that chitotriose and antibodies against midgut glycoproteins inhibited malaria parasite development. Moreover, Shahabuddin and co-workers (46) found in an in vitro assay that P. gallinaceum ookinetes could not bind to Aedes aegypti midguts after chemical modification of epithelial cell surface carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recognition of the gut epithelial cell surface by ookinetes is a crucial step in the life cycle of Plasmodium, little molecular information is available about this process. There is evidence to suggest that carbohydrate components of the gut epithelial cell surface are involved in interactions with the parasite (13,14). However, no candidate glycosylated proteins from the adult Anopheles midgut have been identified.…”
mentioning
confidence: 99%
“…While there is strong evidence that antibodies are the primary mediators of anti-vector transmission-blocking immune responses (28,41,48), the data are not so clear for mosquitocidal immunity, primarily because of the variability in existing reports. All animals used in these mosquitocidal immunity studies were immunized with a mix of crude or partially purified mosquito antigens.…”
Section: Discussionmentioning
confidence: 99%
“…All animals used in these mosquitocidal immunity studies were immunized with a mix of crude or partially purified mosquito antigens. The methods for isolating antigen has varied from using whole ground mosquitoes (1,49) to immunizing with midgut antigens that only bind wheat germ agglutinin (41); also, at least five different mosquito species have been studied. Likewise, the vaccinated host animals ranged from rabbits to guinea pigs to mice, and most studies reported that only one or a few of the animals in the experiment generated an immune response that affected mosquito physiology.…”
Section: Discussionmentioning
confidence: 99%